Revitalisasi Pemikiran Pendidikan Ibnu Khaldun dalam Konteks Pendidikan Alternatif: Tinjauan Konseptual Model Sekolah Rakyat di Indonesia - Nurdin, Nurdin; Hafidzi, Anwar; Makmun, Makmun; Irawan, Bambang (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2025)
This study explores the relevance of Ibn Khaldun’s educational thought to contemporary alternative education practices, particularly the Sekolah Rakyat (People's School) model in Indonesia. As a classical Muslim scholar, Ibn Khaldun emphasized the transformative role of education in shaping individuals and sustaining civilization. Through a qualitative library-based method, this research analyzes key educational concepts from Ibn Khaldun’s Muqaddimah, including his views on the stages of learning, the integration of moral and intellectual development, and the social function of education. These concepts are then conceptually mapped against the philosophical foundations of Sekolah Rakyat, which emphasizes community-based, character-driven, and experiential learning. The study finds significant theoretical alignment between Ibn Khaldun’s ideas and the values promoted in Sekolah Rakyat, particularly in their shared commitment to holistic human development and social justice. The findings contribute to the revitalization of Islamic educational philosophy in contemporary contexts and propose a framework for integrating classical thought into modern alternative education models.